2019
DOI: 10.3390/catal9010066
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenation of Ethanol to Acetaldehyde over Different Metals Supported on Carbon Catalysts

Abstract: Recently, the interest in ethanol production from renewable natural sources in Thailand has been receiving much attention as an alternative form of energy. The low-cost accessibility of ethanol has been seen as an interesting topic, leading to the extensive study of the formation of distinct chemicals, such as ethylene, diethyl ether, acetaldehyde, and ethyl acetate, starting from ethanol as a raw material. In this paper, ethanol dehydrogenation to acetaldehyde in a one-step reaction was investigated by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 35 publications
(53 reference statements)
1
46
0
Order By: Relevance
“…Regarding ethanol, similar processes are assumed to either release a proton or remove an oxygen ion [225], [237]- [239]:…”
Section: Methodsmentioning
confidence: 99%
“…Regarding ethanol, similar processes are assumed to either release a proton or remove an oxygen ion [225], [237]- [239]:…”
Section: Methodsmentioning
confidence: 99%
“…To identify the changes in chemical functional groups, FT-IR technique was employed on MCF-C, MCF-C SP300, MCF-C SP350, and MCF-C SP 400 as seen in Figure 5. The IR spectrum of fresh MCF-C catalyst was well accorded with that reported in the literature [12], having eight IR active elementary bands encountered at 759 cm -1 (C-H vibrations), 1020 cm -1 (C-H vibrations), 1239 cm -1 (O-H blending), 1550 cm -1 (C=C stretching vibrations), 1755 cm -1 (C=O stretching vibrations), 2040 cm -1 (C=C stretching vibrations), 2150 cm -1 (C≡ C stretching vibrations), and 2970 cm -1 (aliphatic C-H) [11,[24][25][26]. For all spent catalysts, the region at 750-800 cm -1 was observed an increase of the peak of (C-H vibrations) suggesting coke formation, especially in MCF-C SP300 catalyst.…”
Section: Catalytic Testmentioning
confidence: 99%
“…Previously, Liu et al [10] reported that ordered mesoporous carbon catalyst essentially catalyzed the dehydrogenation of propane to propylene with high activity. Later, Ob-eye et al [11] also reported that ethanol dehydrogenation to acetaldehyde apparently occurred using activated carbon-promoted with cobalt (Co) having very high selectivity to acetaldehyde. It is also recognized that the mesocellular foam carbon (MCF-C) is one of the robust carbon catalysts, which can be employed in ethanol dehydrogenation in order to produce acetaldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Because of their high selectivity towards acetaldehyde, supported copper catalysts, such as Cu-SiC, [5] Cu/Zeolites, [8] Cu-SiO 2 , [9,10] Cu-Al 2 O 3 , [11] Cu-ZnO-Al 2 O 3 , [12] Cu/ carbon, [13] or Cu/GO, [14] have therefore sparked renewed interest. Cu supported on carbon materials are currently among the most selective catalysts [13,15] because of the relatively inert carbon surface, which limits secondary reactions such as esterification, aldol condensation or ketonization. [9] However, the weak metalsupport interactions and the relatively low melting point of copper make the carbon-supported catalysts particularly prone to sintering.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Additionally, the inert surface of mesoporous carbon can help minimize side reactions to increase the selectivity towards acetaldehyde. [9,13] It has previously been shown that N-doping can increase the metal-support interactions between the metal nanoparticles and the carbon support. [20,21] For instance, Bulushev et al reported N-doping of carbon and the use of the material as a support for Cu nanoparticles in the catalytic decomposition of formic acid.…”
Section: Introductionmentioning
confidence: 99%